Teachers’ Questions in Elementary School English Learning: Types and Functions - Naomi Dwi Aprina; Erna Andriyanti (Indonesian Journal of EFL and Linguistics, 2020)
Question types usually used in classroom learning are display questions and referential questions. Many teachers mostly used display questions in their classroom learning. However, studies showed that display questions limit the students’ opportunity to produce the language. Therefore, this present study aimed to analyse the contribution of teacher questions’ types in English classroom learning to classroom interaction. The participants of this qualitative study were three sixth grade English teachers from three different Islamic schools in Yogyakarta. The data were collected through classroom observation. The result shows that the teachers used both display and referential questions, and all teachers used display questions more frequently. Furthermore, the result of the analysis shows that referential questions received longer responses than display questions. It also indicated that referential questions gave the students more opportunities to practice the language. However, both display questions and referential questions are important for EFL students. The use of both question types can be adjusted based on the levels of the students, the purpose of the lesson and students’ learning strategies.